MFH Mimic in Breast: A High-Grade Malignant Phyllodes Tumor. (17th October 2012) - Hemalatha, A. L.; Sindhuram, V. Sumana; Asha, U.
Abstract : Malignant phyllodes tumor is usually diagnosed by the presence of benign duct-like epithelium and malignant mesenchymal tissue. In addition to the usual fibrosarcomatous features, the mesenchymal component may show areas resembling osteogenic sarcoma, chondrosarcoma, liposarcoma, leiomyosarcoma, rhabdomyosarcoma, malignant mesenchymoma, and, very rarely, malignant fibrous histiocytoma. We present one such rare case of malignant phyllodes tumor with malignant fibrous histiocytoma-like stromal differentiation.